Epipregnanolone as a Positive Modulator of GABAA Receptor in Rat Cerebellar and Hippocampus Neurons - Bukanova, Julia; Solntseva, Elena; Kondratenko, Rodion; Kudova, Eva (Biomolecules, 2021)
Epipregnanolone (3β-hydroxy-5β-pregnan-20-one, Epi) is an endogenous steroid with important physiological effects and high affinity for GABAA receptors. The effect of Epi on GABA-induced chloride current (IGABA) in native neurons has hardly been studied. In this work, we studied the influence of Epi on the IGABA in the Purkinje cells of rat cerebellum and pyramidal neurons of rat hippocampus with the patch clamp technique. We showed that Epi is a positive modulator of the IGABA with EC50 of 5.7 µM in Purkinje cells and 9.3 µM in hippocampal neurons. Epi-induced potentiation of the IGABA was more potent at low vs. high GABA concentrations. Isopregnanolone (3β-hydroxy-5α-pregnan-20-one, Iso) counteracted Epi, reducing its potentiating effect by 2-2.3 times. Flumazenil, a nonsteroidal GABAA receptor antagonist, does not affect the Epi-induced potentiation. Comparison of the potentiating effects of Epi and allopregnanolone (3α-hydroxy-5α-pregnan-20-one, ALLO) showed that ALLO is, at least, a four times more potent positive modulator than Epi. The combined application of ALLO and Epi showed that the effects of these two steroids are not additive. We conclude that Epi has a dual effect on the IGABA increasing the current in the control solution and decreasing the stimulatory effect of ALLO.
Keywords: allopregnanolone; pregnanolon; Pregnanolone; GABA receptor; Rats, Wistar; GABA-A Receptor Agonists; flumazenil patch clamp; Pyramidal Cells; pyramidové buňky; isopregnanolone; potkani Wistar; Cerebellum; receptory GABA-A; agonisté receptorů GABA-A; krysa rodu Rattus; Hippocampus; Animals; zvířata; Rats; mozeček; Receptors, GABA-A; epipregnanolone; hipokampus